History Of Early Breastfeeding Initiation And Food Intake With The Even Stunting Of Children Aged 6-59 Months - Dahliansyah Dahliansyah (Jurnal teknologi Kesehatan Borneo, 2020)
Stunting and other forms of malnutrition are the principal factors causing child death, disease, and disability. Stunting in infants is a failure to grow because of a history of insufficient nutrition for a long time. Toddlers will be said to experience stunting permanently and are difficult to repair when they reach the age of 2 years, so the stunting management is directed to the golden period (0-24 months). This research finds out the relationship between Early Breastfeeding Initiation and Food Intake and the incidence of Stunting. Analytical observational research method with cross-sectional design. The population of this research is all children under five after 6-59 months near Kelantan Siantan, Pontianak City. The number of samples in this study amounted to 94 people using a purposive sampling technique. The results showed that there was a significant relationship (p <0.05) between IMD and the incidence of stunting. Toddlers who get IMD at birth have a 0.3 times chance of not getting stunted compared to those who did not get IMD (OR = 0.323 CI95% = 0.124 to 0.842). There was a significant relationship (p <0.05) between food intake and the incidence of stunting, toddlers who were given good food intake were 0.3 times less likely to experience stunting compared to those who received inadequate food intake (deficits).